Empirical test of the trust–performance link in an international alliances context - Silva, Susana Costa e (2014)
Despite the widespread use of trust as a determinant of successful relationships, limited empirical evidence exists to substantiate a positive relationship between trust and performance. Thus, the purpose of this study is to investigate the antecedents of trust and to examine the trust–performance relationship in international alliances. The conceptual model was tested empirically using primary data collected from 232 international alliances involving Portuguese and international firms. The results reported suggest that when controlling for the experience and size of a firm, trust has a strong and positive effect on performance. Key antecedents identified as significant influencers on trust are shared values, communication and opportunistic behaviour. Additionally, interaction effects are identified, indicating that similarities among partners enhance the positive relationship between trust and performance.